Biometric technologies for interoperability financial and security in the metaverse - Cobos Gutierrez, Carlos Eduardo (2025)
Objective: The objective of this study was to examine of manner quantitatively how biometric technologies can improve financial interoperability in the metaverse. The impact of facial recognition and biometric authentication on security perceptions, user experience, and usage intent in virtual environments was analyzed, as well as the relationship between security perceptions and users' willingness to adopt these technologies in their financial transactions. Materials and methods: A quantitative method was used with a non-experimental, cross-sectional, and descriptive design. Surveys were applied to 150 participants, including financial technology experts and active users of the metaverse. The key variables, such as perception of security, ease of use, and adoption intention, were measured using Likert-type scales and analyzed using descriptive and inferential statistics, including correlation coefficients and reliability analysis through of the alpha of Cronbach's. Results: The results showed a significant positive correlation (r = 0.78; p < 0.001) between the perception of security and the intention to use these technologies. 92% of participants signaled improved security as their primary benefit, and 90% highlighted faster transaction times. The scales used were highly reliable (α > 0.87), demonstrating the consistency of the instruments employed. Conclusions: It is conclusion is that biometric technologies are an effective solution for improving financial interoperability in the metaverse, as a positive perception of security significantly increases adoption intention. Furthermore, the need to establish regulations and ethical standards to guarantee data privacy is highlighted. Implementing these technologies in financial institutions would not only optimize their services but also strengthen user trust and engagement in digital environments.